The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/ijn.s146546
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro and in vivo protein release and anti-ischemia/<br />reperfusion injury properties of bone morphogenetic protein-2-loaded glycyrrhetinic acid-poly(ethylene glycol)-b-poly(L-lysine) nanoparticles

Abstract: Here, we describe a bone morphogenetic protein-2 (BMP-2) nanocarrier based on glycyrrhetinic acid (GA)-poly(ethylene glycol) (PEG)-b-poly( l -lysine) (PLL). A protein nanocarrier was synthesized, characterized and evaluated as a BMP-2 delivery system. The designed nanocarrier was synthesized based on the ring-opening polymerization of amino acid N-carboxyanhydride. The final product was measured with 1 H nuclear magnetic resonance. GA-PEG-b-PLL nanocarrier could co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…There are about a hundred published release studies with BMP-2 every year. In many cases, the release studies are carried out in PBS without any solubility increasing additives [9][10][11][12][13][14][15][16]. However, there are only a few publications that refer to the low solubility of the protein and the associated potential influence, both on the release itself (violation of sink conditions), and on the quantification of the partially aggregated protein [17].…”
Section: Introductionmentioning
confidence: 99%
“…There are about a hundred published release studies with BMP-2 every year. In many cases, the release studies are carried out in PBS without any solubility increasing additives [9][10][11][12][13][14][15][16]. However, there are only a few publications that refer to the low solubility of the protein and the associated potential influence, both on the release itself (violation of sink conditions), and on the quantification of the partially aggregated protein [17].…”
Section: Introductionmentioning
confidence: 99%
“…33 Furthermore, the micellar delivery system may provide more drug accumulated in bone tissues due to its nanosize effect. 34 Therefore, it represents a more effective and safe treatment compared to repeated local injections. Moreover, it was first reported that polymeric biomaterials combined with NOB and it made a suitable candidate for BTE.…”
Section: Introductionmentioning
confidence: 99%
“…Even though BMP‐2 is already applied in clinical practice, not many studies have been done to determine their release profile in vivo . Most of the currently available data are dealing with in vitro studies .…”
Section: Introductionmentioning
confidence: 99%